SPATIAL THINKING SKILL GURU GEOGRAFI DI PROVINSI BALI - Astawa, Ida Bagus Made; Sarmita, I Made; Nugraha, A Sediyo Adi (JURNAL WIDYA LAKSANA, 2019)
This Community service aims to develop a spatial thinking skills of geography teacher in the province of Bali that are designed in the form of education and training. Participants were 50 geography teachers in nine districts / cities in the province of Bali. Education and training was provided with discourse, discussion and workshop methods. An understanding of the spatial thinking skills of teachers was evaluated using a test, while for RPP it was produced using an observation sheet (APKCG modification), as well as a questionnaire to measure the usefulness of education and training. The results of the evaluation of education and training conducted indicate that: (1) The average value of Spatial Thinking Skills for senior high school Geography teachers in Bali Province is categorized very high (85.93). The implementation of the high competency spatial thinking skills is also reflected in the well-categorized of RPP (4.75); and (2) education and training to develop of Spatial Thinking skills for senior high school Geography teachers in Bali Province is considered to have a very high useful value (4.98), especially as a vehicle for the formation of spatial insights of students.